Meningkatkan Konsep Trigonometri Berbasis Nilai Keislaman Melalui Buku Saku - Nova Nindarti; Suherman Suherman; Syaiful Anwar (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
Trigonometry is one of mathematics material that is discussed about angels and the measuring of the angels. The application of trigonometry in daily life such us made of buildings. Architectural could not be able to build the buildings without the application of trigonometry. This research was aimed to know the improving concept of trigonometry for students by learning trigonometry with pocketbook assistance based on Islamic value. The research was conducted in SMAN 2 Liwa, West Lampung on April 2018. The aspect that was tested in this research was the improving concept of trigonometry for students. This research used experimental method according to quasi experimental design based on nonequivalent control group design. Technique sampling that was used cluster sampling technique. The research was begun by given pretest, then learned concept of trigonometry by using pocketbook based on Islamic value, and given post-test in the last learning in order to see the improving concept of trigonometry by pretest and posttest.